2022
DOI: 10.1111/jopr.13620
|View full text |Cite
|
Sign up to set email alerts
|

Full arch immediate occlusal loading using site specific implants: A clinical series of 10 patients (13 arches)

Abstract: Osseointegration of dental endosseous implants has proven to be effective, predictable, and clinically successful. Unloaded healing protocols were originally used in treating edentulous patients. Full arch immediate occlusal loading protocols have been shown to be as effective as unloaded healing protocols. This paper reports on the results, benefits, and limitations of one specific immediate loading protocol using site specific implants for fresh extraction and healed extraction sites. Materials and methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…In a clinical series involving dental implants and immediate loading for the management of edentulous patients, the results demonstrated a 100% survival rate for both implants and prosthetics. The study indicated that the protocol can be used with a high level of anticipated success [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical series involving dental implants and immediate loading for the management of edentulous patients, the results demonstrated a 100% survival rate for both implants and prosthetics. The study indicated that the protocol can be used with a high level of anticipated success [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies reported favorable long-term evidence of fixed prosthetic rehabilitation by immediate loading of implants. This clinical protocol can be a general treatment strategy for fully edentulous arches in geriatric patients [37][38][39]. However, the available evidence suggests that a higher incidence of biological and technical complications is reported with complete-arch fixed dental prostheses [33,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…From the statistical analysis performed, it appears that, for the analyzed cases, the degree of ossification (Ca/P ratio) was better represented for the immediate loading, compared to the late loading. Currently, immediate loading [14][15][16][17] is increasingly used with good long-term results, but also for the fastest possible reintegration of patients into society.…”
Section: Discussionmentioning
confidence: 99%